Analisis Penerapan Tata Kelola dalam Pengelolaan Aset Tetap Daerah: Studi Kasus pada Pemerintah Daerah Kabupaten Kulon Progo - Assa, Sekar Bening Milenia; Halim, Abdul (ABIS: Accounting and Business Information Systems Journal, 2026)
Purpose – This study aims to analyze the causes of persistent problems in fixed asset management in the Kulon Progo Regency Government and describe the implementation of fixed asset management governance in Kulon Progo Regency. Research Method – This study uses a qualitative method with a case study approach. Data were collected through semi-structured interviews and analysis of relevant documents. Findings – The results of the study show that the problems of fixed asset management in Kulon Progo Regency are not only technical in nature, but also include limitations in human resources, administrative irregularities, legalization constraints, budget limitations, and regulatory inconsistencies. The Kulon Progo Regency Government has attempted to implement transparent and accountable asset governance, but its implementation is still formalistic in nature. Limitations/Implications – This study is limited by access to and completeness of supporting documents as well as the number of respondents interviewed. This study shows that effective asset governance stems from the government's role as a steward protecting long-term public interests, not merely as an enforcer of rules. Originality – This study updates previous studies by applying stewardship theory as the basis for analysis and nine governance principles as an evaluation tool in assessing asset management practices in Kulon Progo.